(untitled) (Sapientia, 2021)
How easy is it to construct life and consciousness from the building blocks of reality? Some philosophers seem to think both are pretty easy, whilst others take consciousness to be difficult but life to be no problem. In this paper I question whether we should in fact think this, could life after all be difficult to construct? I contend that the answer to this, much like the answer to how hard consciousness is to construct, largely depends on the nature of life and the building blocks of reality. I will show that many of the considerations as to whether consciousness is hard to construct can be paralleled when thinking about the construction of life, and that given one prominent definition of life, it does in fact seem difficult to construct. I will conclude by offering a few suggestions for future research, and suggest that philosophers should be more hesitant in their affirmation that life is easy to construct.